2015
DOI: 10.1016/j.toxlet.2015.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum stress and oxidative stress are involved in ZnO nanoparticle-induced hepatotoxicity

Abstract: Zinc oxide nanoparticles (Nano-ZnO) are widely used in sunscreens, clothes, medicine and electronic devices. However, the potential risks of human exposure and the potential for adverse health impacts are not well understood. Previous studies have demonstrated that exposure to Nano-ZnO caused liver damage and hepatocyte apoptosis through oxidative stress, but the molecular mechanisms that are involved in Nano-ZnO-induced hepatotoxicity are still unclear. Endoplasmic reticulum (ER) is sensitive to oxidative str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
90
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(101 citation statements)
references
References 52 publications
(93 reference statements)
8
90
0
2
Order By: Relevance
“…The effect of ZnO-NPs on serum ALT, AST, albumin, total protein and liver MDA indicated that the liver is one of the target organs of such NPs toxicity. Similar effects of ZnO-NPs on serum ALT, AST, and MDA levels were reported [4,34,50,58]. Also, the significant decrease of the total serum proteins and albumin caused by ZnO-NPs agreed with Wang et al (2010) [57] and Al-Rasheed et al (2012) [2].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The effect of ZnO-NPs on serum ALT, AST, albumin, total protein and liver MDA indicated that the liver is one of the target organs of such NPs toxicity. Similar effects of ZnO-NPs on serum ALT, AST, and MDA levels were reported [4,34,50,58]. Also, the significant decrease of the total serum proteins and albumin caused by ZnO-NPs agreed with Wang et al (2010) [57] and Al-Rasheed et al (2012) [2].…”
Section: Discussionsupporting
confidence: 82%
“…Similar effects on the serum albumin and total protein levels were demonstrated by Wang et al (2010) [57] and AlRasheed et al (2012) [2]. Also similar effects on serum ALT and AST were reported [2,57,58,62]. Furthermore, serum total proteins and albumin levels in spite of elevation were still significantly lower than those of the control group and vitamin E control group, while serum ALT and AST levels reached non-significant levels compared to the control group and vitamin E control group.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Zinc oxide nanoparticles (Nano-ZnO), which are widely used in daily commodities, have been reported to induce hepatotoxicity through ER stress. ER swelling and ribosomal degranulation were also observed by TEM in the liver tissues treated with Nano-ZnO [26]. Obvious ER aggregation and the associated swelling were also observed in nano-ZnO treatment of human umbilical vein endothelial cells (HUVECs) [27].…”
Section: Uptake Of Enps and Their Intracellular Localizationsmentioning
confidence: 99%
“…Oxidative stress, the inhibition of protein glycosylation, a reduction in disulde bond formation, calcium depletion and accumulation of unfolded proteins in the ER lumen may disrupt the ER function, and trigger the unfolded protein response (UPR), also known as "ER-stress". 46 Recently, ROS have emerged as important regulators of ER function and UPR activation in several diseased conditions. 47 GRP78 protein was widely known as an ER stress marker.…”
Section: Discussionmentioning
confidence: 99%